2021
DOI: 10.1111/jch.14209
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension‐mediated organ damage regression associates with blood pressure variability improvement three years after successful treatment initiation in essential hypertension

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…However, little is known about the associations between longitudinally assessed differences in BPV and the changes in HDMO. The paper of Triantafyllidi et al 10 published in the current issue of the Journal adds a new piece of evidence in this scenario, showing that the short‐term BPV reduction (Delta BPV) obtained after 3 years of successful antihypertensive therapy was related to a decrease in left ventricular mass (Delta LVMI), independently of the baseline average BPs and other potential confounding factors. 10 This was true only in the subgroup (n = 119) of well‐controlled hypertensive subjects belonging to an overall population of 180 newly diagnosed and never‐treated hypertensive patients.…”
Section: Short‐term Blood Pressure Variability and Subclinical Organ Damagementioning
confidence: 97%
See 3 more Smart Citations
“…However, little is known about the associations between longitudinally assessed differences in BPV and the changes in HDMO. The paper of Triantafyllidi et al 10 published in the current issue of the Journal adds a new piece of evidence in this scenario, showing that the short‐term BPV reduction (Delta BPV) obtained after 3 years of successful antihypertensive therapy was related to a decrease in left ventricular mass (Delta LVMI), independently of the baseline average BPs and other potential confounding factors. 10 This was true only in the subgroup (n = 119) of well‐controlled hypertensive subjects belonging to an overall population of 180 newly diagnosed and never‐treated hypertensive patients.…”
Section: Short‐term Blood Pressure Variability and Subclinical Organ Damagementioning
confidence: 97%
“… 10 This was true only in the subgroup (n = 119) of well‐controlled hypertensive subjects belonging to an overall population of 180 newly diagnosed and never‐treated hypertensive patients. 10 …”
Section: Short‐term Blood Pressure Variability and Subclinical Organ Damagementioning
confidence: 97%
See 2 more Smart Citations
“…Analyzing the factors related to sepsis organ function injury can provide more clinical prevention and sepsis-related organ function injury targets and better predict patients' prognosis. Studies have shown that blood pressure variability (BPV) is related to organ function injury in various diseases, but relevant studies focus mainly on patients with cardiovascular diseases (1)(2)(3). The common pathophysiological basis of functional injury of related organs caused by sepsis is that patients cannot maintain blood pressure and withstand the attack of many inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%